Slavoj Žižek - Myers, Tony, 1969- (Routledge critical thinkers., 2003)
Tony Myers provides a clear and engaging guide to Zizek's key ideas, explaining the main influences on Zizek's thought, most crucially his engagement with Lacanian psychoanalysis, using examples drawn from popular culture and everyday life.